Self-initiated management approaches in everyday occupations used by people with acquired cognitive impairment. (17th February 2022) - Nygård, Louise; Ryd, Charlotta; Astell, Arlene; Nedlund, Ann-Charlotte; Boger, Jennifer; Mäki Petäjä Leinonen, Anna; Issakainen, Mervi; Larsson Lund, Maria
Abstract: Background: Striving to cope with day-to-day challenges is a basic human behaviour. Self-initiated management approaches provide a resource that has yet to be discovered and systematically used in occupational therapy practice. This resource might be especially important for people with dementia who are less likely to adopt management approaches initiated by others. Aims/objectives: Based on the findings of former studies on management and problem-solving actions among people with cognitive impairment, this article aims to identify and categorize the study participants' self-initiated management approaches and how these may be manifested in strategies in everyday occupations. Material and methods: The study utilized a form of meta-synthesis; an aggregated analysis, where findings from 11 studies published 2004–2020 were compared and categorized, incorporating the views of participants with dementia/mild cognitive impairment, or acquired brain injury. Results: Thirty strategies were identified and grouped into seven categories of management approaches, used in a variety of everyday occupations and situations. A majority of the strategies were found in both populations, suggesting that management approaches are more similar than different across populations with cognitive impairment. Conclusions and significance: Attending to the rich variation of self-initiated management approaches/strategies among persons with cognitive impairment offers possibilities for developing occupational therapy interventions.